Trapping of Microplastics in Halocline and Turbidity Layers of the Semi-enclosed Baltic Sea - Zhou, Qian; Tu, Chen; Yang, Jie; Fu, Chuancheng; Li, Yuan; Waniek, Joanna J. (Frontiers in Marine Science, 2021)
Microplastic pollution in semi-enclosed seas is gaining attention since microplastics are more likely to accumulate there. However, research on the vertical distribution of microplastics and impact factors is still limited. In this study, we focus on the Baltic Sea, which has distinguished salinity stratification, and we assume that the resulting strong density stratification (halocline) can influence the vertical distribution of microplastics in the water column. Therefore, we analyzed the vertical abundance distribution, the composition, and the sizes of microplastics (27.3–5,000.0 μm) in the Baltic Sea. The results showed that microplastics comprising fibers, fragments, and films occurred throughout the water column at an abundance of 1.1–27.7 items L−1. The abundance of microplastics (3.2–27.7 items L−1) at haloclines was significantly higher than those at other water depths except the near surfaces (p < 0.05), contributing 24.1–53.2% of the microplastics in the whole water column. Small microplastics (<100 μm) were more likely to accumulate in the water layers above halocline. Moreover, the current with high turbidity might be another carrier of microplastics in the near-bottom water layer due to its strong correlation with microplastics abundance. This study provides valuable evidence for the accumulation trend of microplastics in water columns and its influencing factors in the semi-enclosed marginal sea. Further research on the vertical distribution of microplastics under the control of multiple factors should be conducted in the future.